Quarenteners vs. Cloroquiners: a framework to analyze the effect of political polarization on social distance stances - Ebeling, Régis; Sáenz, Carlos Córdova; Nobre, Jeferson Campos; Becker, Karin (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2020: Anais do VIII Symposium on Knowledge Discovery, Mining and Learning, 2020)
The worldwide COVID-19 pandemic has struck people’s lives overnight. With an alarming contagious rate and no effective treatments or vaccines, it has evoked all sorts of reactions. In this paper, we propose a framework to analyze how political polarization affects groups’ behavior with opposed stances, using the Brazilian COVID polarized scenario as a case study. Two Twitter groups represent the pro/against social isolation stances referred to as Chloroquiners and Quarenteners. The framework encompasses: a) techniques to automatically infer from users political orientation, b) topic modeling to discover the homogeneity of concerns expressed by each group; c) network analysis and community detection to characterize their behavior as a social network group and d) analysis of linguistic characteristics to identify psychological aspects. Our main findings confirm that Cloroquiners are right-wing partisans, whereas Quarenteners are more related to the left-wing. The political polarization of Chloroquiners and Quarenteners influence the arguments of economy and life, and support/opposition to the president. As a group, the network of Chloroquiners is more closed and connected, and Quarenteners have a more diverse political engagement. In terms of psychological aspects, polarized groups come together on cognitive issues and negative emotions.